Večno mladi Htinj : ob 80-letnici Janka Čara - Marina Bajić; Jesenšek, Marko (2012)
Eternal Youthful Htinj: at the 80th Anniversary of Janko Čar. Monograph Eternally Young Htinj is dedicated to the 80th anniversary of Janko Čar, one of the founders of Mariborian Slovene studies and a lecturer of Slovene at the Faculty of Education and the Faculty of Education, University of Maribor, the forerunner of today's Faculty of Arts. At the beginning of his academic career, Janko Čar covered virtually every field of teaching Slovene, namely literary language, history of language and stylistics, thus approaching issues of Slovene literature. On the occasion of his high life anniversary, we prepared a monograph in which the members of the Department of Slavic Languages ​​and Literatures present their research results. The idea is to cover, in individual chapters, those areas in which Janko Čar was engaged in research or teaching, thus showing the growth of Mariborian Slovene studies from its beginnings, when professors were still active. i. to the present day, when the Department's employees are narrowly specialized in particular fields of language and literature. The monograph presents those areas of the Slovene language that make Mariborian Slovene today recognizable in Slovene and also present internationally. The first place is definitely the history of the Slovene language and dialectology (the well-known Mariborian dialectological school), the fields in which Mariborian Slovene studies is the leading country in the country and, because it is a national language, also in the world. This is followed by presentations of linguistic culture and cultural history, orthodoxy, stylistics (and thus literary sciences), and sociolinguistics. areas developed by Janko Čar as one of the pioneers of Mariborian Slovene studies, and then the monograph reaches out to the field of literature through orthography, lettering and word formation and presents the latest research results of Mariborian Slovene studies.